The Influence of Service Quality and Brand Image on Loyalty Through Satisfaction Grab-Bike Customers in Bekasi City - Rahajeng Ariyani; Agus Riyanto; Efendi Efendi (Majalah Ilmiah Bijak, 2021)
The purpose of this study was to determine and analyze the effect of Service Quality and Brand Image on the loyalty of users of the online Grab bike Ojek transportation service through customer satisfaction as an intervening variable. The population in this study was Grab bike users in the city of Bekasi, with 200 respondents. This study uses non - probability sampling with SEM research methods assisted by the LISREL version 8.8 program as a data processing instrument. The results show that service quality and brand image have a direct effect on customer satisfaction. Another conseque nce of this study is that brand image has an indirect impact on customer loyalty. Quality directly affects customer loyalty through customer satisfaction and service, with customer satisfaction as an intervening variable.